Enabling the Business of Agriculture 2019 - World Bank (World Bank, Washington, DC, 2019)
Enabling the Business of Agriculture 2019 presents indicators that measure the laws, regulations and bureaucratic processes that affect farmers in 101 countries. The study covers eight thematic areas: supplying seed, registering fertilizer, securing water, registering machinery, sustaining livestock, protecting plant health, trading food and accessing finance. The report highlights global best performers and countries that made the most significant regulatory improvements in support of farmers.